Do the plea of inadmissibility of the action and the dismissal of the action regulate the same assumptions of application? Analysis of their application in the intermediate stage - Cabrera Villa, Richard Alexander (2024)
The purpose of this article is to analyze the application of the exception of inadmissibility of the action in the intermediate stage and its collision with the assumption of dismissal regulated in paragraph b of numeral 2 of article 344 of the Procedural Code. The study will have as a starting point the old criminal procedural regime applied in the Republic of Peru, to then consider comparative regulations of other countries, some of them with an accusatory-guarantist influence regarding the application of the punitive penal process, such as the Chilean Procedural Code of 2002, the Colombian Code of Criminal Procedure of 2004, the Argentinean Code of Criminal Procedure of 2014, the 1998 Code of Criminal Procedure of Paraguay, the 2000 Code of Criminal Procedure of Ecuador, the 2001 Organic Code of Criminal Procedure of Venezuela, the 1999 Code of Criminal Procedure of Bolivia, the 1998 Code of Criminal Procedure of Costa Rica, the 1998 Code of Criminal Procedure of El Salvador, the 2008 Code of Criminal Procedure of Panama and the 2002 Code of Criminal Procedure of Honduras. Subsequently, a description is made of the essential notes of the exception of inadmissibility of action and dismissal from the point of view of doctrine and jurisprudence, to finally compare the assumptions of application of both institutions and arrive at the respective conclusions for a better understanding of them.